The affiliation of Hexasterias problematica and Halodinium verrucatum sp. nov. to ciliate cysts based on molecular phylogeny and cyst wall composition - Gurdebeke, Pieter R.; Mertens, Kenneth; Takano, Yoshihito; Yamaguchi, Aika; Bogus, Kara; Dunthorn, Micah; Matsuoka, Kazumi; Vrielinck, Henk; Louwye, Stephen (European Journal of Protistology, 2018)
Species in the genera Hexasterias and Halodinium have been recorded over the last decades as acritarchs in palynological and/or plankton studies. In paleoenvironmental studies, these resting stages are often interpreted as indicators of freshwater input. The biological affinity of these genera has never been definitely established. Here, a new species, Halodinium verrucatum sp. nov., is described and molecular evidence (single specimen SSU and LSU rDNA sequencing) reveals that both this new species and Hexasterias problematica, collected from sediment samples in the Skagerrak and Baltic Sea, are resting stages of prorodontid ciliates. Additionally, infrared spectroscopic analysis (micro-FTIR) of Hexasterias problematica and Halodinium spp. specimens indicates a carbohydrate-based composition of the cyst wall with evidence for nitrogen-containing functional groups. A similar composition is recorded for tintinnid loricae, which further supports the placement of Hexasterias and Halodinium as ciliate cysts, and the composition is consistent with the heterotrophic nature of ciliates. The morphologically similar species Radiosperma corbiferum has a comparable composition, suggesting a similar ciliate affinity and indicating the utility of micro-FTIR in understanding acritarch affinity. Hexasterias problematica typically occurs in coastal waters from temperate to arctic regions. Halodinium verrucatum sp. nov. is observed in temperate estuarine sediments in the northern hemisphere.